STATE, PROBLEMS, WAYS TO REDUCE THE PRODUCTION LEVEL INJURIES IN THE INDUSTRY OF HOUSING AND UTILITIES IN UKRAINE - Serikov, Ya. O. (Municipal economy of cities. Series: «Economy science», 2025)
Today, the state of industrial injuries is a problem in all countries of the world. This is determined by statistical data of the International Labor Organization (ILO) and the World Health Organization (WHO). According to the data of these organizations, about 270 million accidents occur in the «man - industrial environment» system in all cranes of the world every year, and about 2.3 million men and women die as a result of occupational diseases. This determines the high urgency of solving the problem of preserving the health of employees. The solution of the considered problem is especially important for our country. According to the data of the Main Department of State Labor of Ukraine, during 2021 to 2023, not only is there a significant level of injury, but also an increase in its level. Data on injuries with fatal consequences are the most representative. The conducted studies revealed that the main causes of injuries of this class of consequences in production conditions include: organizational reasons (violation of safety rules prescribed in technological maps, non-compliance with the requirements of labor protection instructions), violation of safety requirements during work, operation of equipment, especially those , belonging to the category «With increased danger»; technical reasons (unsatisfactory technical condition of the means of production, imperfection of the technological process); psychophysiological reasons (personal and intentional carelessness of the victim, insufficient psychological preparation of the employee for the work he performs). At the same time, the violation of organizational measures for labor protection, as the cause of an accident, in total amounts to about 80%. In the field of housing and communal services of Ukraine, the level of fatal injuries increased by 45-50% during the specified period. A feature of the production activity of enterprises in the field of housing and communal services in our country is a significant list of types of work on which they are performed. It is characteristic that employees who have not undergone appropriate occupational safety training often perform high-risk work at enterprises servicing the territory of the city. This fact determines the occurrence of a fairly significant number of accidents. The main directions for solving the problem under investigation are the involvement of third-party contractors who have appropriate education in the work of this category, as well as the introduction of a system of employee motivation at the enterprise. Such measures do not require significant financial costs and can be implemented in a short time.